Advances in management accounting. - Epstein, Marc J.; Malina, Mary A. (Advances in management accounting,, 2016)
Advances in Management Accounting publishes thoughtful, well-developed articles across a broad spectrum of current topics in the field of management accounting, using a variety of research methods including survey research, field tests, corporate case studies and modeling. Volume 27 exemplifies the broad scope of Advances in Management Accounting, examining a number of areas within management accounting.